PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN: TANGGUNG JAWAB SOSIAL SEBAGAI VARIABEL MODERATING - Rahmatia, Tri Lasita; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence of managerial ownership to the firm value with thecorporate social responsibility as the moderating variable on the non-financial state-owned enterprises (BUMN)companies which are listed in Indonesia stock exchange (IDX) in 2010-2013 periods. The samples are 8 nonfinancialstate-owned enterprises (BUMN) companies which are listed in Indonesia Stock Exchange (IDX) withthe numbers of observation are 32 and they have been selected by using purposive sampling. The result of theresearch which is done by using multiple linear regressions shows that the managerial ownership does not haveany influence to the firm value. Meanwhile, the analysis of the moderating variable which has been done byusing the interaction test method of Moderated Regression Analysis (MRA) shows that corporate socialresponsibility cannot moderate the influence of managerial influence to the firm value therefore it cannotincrease the firm value.Keywords: Managerial Ownership, Firm Value, corporate social responsibility.